RhoH participates in a multi-protein complex with the zinc finger protein kaiso that regulates both cytoskeletal structures and chemokine-induced T cells. (4th May 2018) - Mino, Akihisa; Troeger, Anja; Brendel, Christian; Cantor, Alan; Harris, Chad; Ciuculescu, Marioara F.; Williams, David A.
ABSTRACT: RhoH is a haematopoietic -specific, GTPase-deficient Rho GTPase that plays an essential role in T lymphocyte development and haematopoietic cell migration. RhoH is known to interact with ZAP70 in T cell receptor (TCR) signaling and antagonize Rac GTPase activity. To further elucidate the molecular mechanisms of RhoH in T cell function, we carried out in vivo biotinylation and mass spectrometry analysis to identify new RhoH-interacting proteins in Jurkat T cells. We indentified Kaiso by streptavidin capture and confirmed the interaction with RhoH by co-immunoprecipitation. Kaiso is a 95 kDa dual-specific Broad complex, Trantrak, Bric-a-brac/Pox virus, Zinc finger (POZ-ZF) transcription factor that has been shown to regulate both gene expression and p120 catenin-associated cell-cell adhesions. We further showed that RhoH, Kaiso and p120 catenin all co-localize at chemokine-induced actin-containing cell protrusion sites. Using RhoH knockdown we demonstrated that Kaiso localization depends on RhoH function. Similar to the effect of RhoH deficiency, Kaiso down-regulation led to altered cell migration and actin-polymerization in chemokine stimulated Jurkat cells. Interestingly, RhoH and Kaiso also co-localized to the nucleus in a time-dependent fashion after chemokine stimulation and with T cell receptor activation where RhoH is required for Kaiso localization. Based on these results and previous studies, we propose that extracellular microenvironment signals regulate RhoH and Kaiso to modulate actin-cytoskeleton structure and transcriptional activity during T cell migration.